2017
DOI: 10.1108/ijchm-09-2015-0472
|View full text |Cite
|
Sign up to set email alerts
|

The leading causes and consequences of citizenship pressure in the hotel industry

Abstract: Purpose -This study aims to examine the causes of citizenship pressure and to investigate the relationship between citizenship pressure, job stress, and turnover intentions. Specifically, the current study examines the effects of the personality trait of neuroticism and the organizational cultures of bureaucracy and the market.Design/methodology/approach -Data were collected from 224 hotel employees in the People's Republic of China using a self-administered survey questionnaire. The participants completed mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…Recent research noted that personality traits matter in employees' perception of work pressure and their stress appraisal and coping processes (Carver and Connor-Smith, 2010). For example, employees with the personality trait of neuroticism tend to experience more citizenship pressure (Youn et al, 2017). Moreover, meta-analysis (Feist, 1998) and empirical studies (Herrmann and Felfe, 2014;Coelho et al, 2018) both highlighted the effects of several personality traits on employee creativity.…”
Section: The Moderating Role Of Negative Affectmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research noted that personality traits matter in employees' perception of work pressure and their stress appraisal and coping processes (Carver and Connor-Smith, 2010). For example, employees with the personality trait of neuroticism tend to experience more citizenship pressure (Youn et al, 2017). Moreover, meta-analysis (Feist, 1998) and empirical studies (Herrmann and Felfe, 2014;Coelho et al, 2018) both highlighted the effects of several personality traits on employee creativity.…”
Section: The Moderating Role Of Negative Affectmentioning
confidence: 99%
“…Prior research on OCB—“individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in aggregate promotes the effective functioning of the organization” ( Organ, 1988 , p. 4)—has advocated its positive influences on employees and organizations. However, in recent years, there is an emerging stream of research starts to question the exclusive discretionary nature of OCB ( Youn et al, 2017 ; Germeys et al, 2019 ) and examine the potential negative consequences of OCB ( Deery et al, 2017 ; De Clercq et al, 2019 ; He et al, 2019a ). In particular, the destructive effects of the enforced/non-voluntary version of citizenship behavior, which was described by Vigoda-Gadot (2006) as CCB, have attracted considerable attention from OB and human resource management (HRM) scholars (e.g., Zhao et al, 2014 ; He et al, 2018 , 2019a ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another identified group in this cluster (red) is a group of publications with a selective approach on psychological issues of workers Datta; Singh (2018), Zhao et al (2016) and Youn et al (2017). In the first place, Datta and Singh (2018) studied the climate perceived by hospitality employees in luxury hotels in India, and they specified four dimensions of climate: "esprit of profession, organization, and workgroup"; "leader facilitation and support"; "cohesion, clarity and objectivity of system" and "job challenge, variety and feedback".…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%
“…Moreover, Zhao and Ghiselli (2016) took into consideration the specific characteristics of tourism and hospitality jobs and illustrated the significant buffering impact of hospitality characteristics on job stress. In a study of hotel employees in China, Youn et al (2017) found that citizenship pressure significantly increases job stress among hotel employees. It appears that several other factors in terms of abusive supervision (Harms et al, 2017), surface acting (Geng et al, 2014), team personal and team task conflict (Hon and Chan, 2013), JC and OC (Tiyce et al, 2013) and emotional labor (Jung and Yoon, 2014) are key sources of stress among tourism and hospitality employees.…”
Section: Literature Reviewmentioning
confidence: 99%